Birdwatching Potency at Liwa Botanical Garden, West Lampung - Agis Agita; Nuning Nurcahyani; M. Kanedi; Hendri Busman (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2020)
The Liwa Botanical Garden is located in Kubu Perahu Village, Balik Bukit District, West Lampung Regency. The Liwa Botanical Garden has an area of 86 ha, build in 2007 with the theme of Indonesian Ornamental Plants. The Liwa Botanical Garden is one of the destinations that is being developed for tourism activities and used as a recreational object. One of the functions of the Liwa Botanical Garden is as a tourist spot. Plants in the Liwa Botanical Garden are so beautiful. The Liwa Botanical Garden is a bird habitat because it has an abundant source of food for birds. Therefore it is necessary to do an inventory of bird species by conducting research to find out potential bird species that are used as tourist attractions (birdwatching) at the Liwa Botanical Garden. This research was conducted on October 2019. The method used was the point count method and rapid assessment. Based on field observations found 14 species of birds that are not protected and only 1 species of birds included in the protected category. And found 8 types of plants, namely 5 types of trees, 1 species of ferns, 1 species of bushes, and 1 type of reeds.